The Effect of Temperature and Mass on the viscosity of Oil Fluid by Falling Ball Method - Pamungkas, Andy Bayu; Haryanto, Haryanto (International Journal of Education, Information Technology, and Others, 2025)
Viscosity is an important property of a fluid that indicates resistance to flow due to internal friction forces between molecules. This study aims to measure the viscosity of five types of oil using the falling ball method based on the principle of Stokes' Law and analyze the effect of temperature on viscosity values. A metal ball was dropped into the oil liquid in a transparent tube, and the travel time of the ball was recorded at five temperature variations: 30°C, 40°C, 50°C, 60°C, and 70°C. The measurement results showed that the higher the temperature of the liquid, the lower the viscosity. The average viscosity obtained was 131.764 cm²/s, with the highest value at 30°C. Among the oil brands tested, Oli(D) showed the highest viscosity at all temperatures. The study also found that increasing the number of dropped balls can increase the temperature of the liquid due to friction, which in turn decreases the viscosity. Thus, the dropped ball method proved to be effective in viscosity measurement, although accuracy is highly dependent on the accuracy of time recording. This research also confirms the importance of selecting lubricants that are suitable for viscosity characteristics for machinery and industrial applications.